2018
DOI: 10.1371/journal.pone.0194372
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of codon usage bias in four sequenced cotton species

Abstract: Codon usage bias (CUB) is an important evolutionary feature in a genome which provides important information for studying organism evolution, gene function and exogenous gene expression. The CUB and its shaping factors in the nuclear genomes of four sequenced cotton species, G. arboreum (A2), G. raimondii (D5), G. hirsutum (AD1) and G. barbadense (AD2) were analyzed in the present study. The effective number of codons (ENC) analysis showed the CUB was weak in these four species and the four subgenomes of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
121
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(134 citation statements)
references
References 69 publications
12
121
1
Order By: Relevance
“…Similarly, the M gene ENc value in SARS‐CoV‐2 was decreased by an amount of 3 to 5. Genes with low expression levels have high ENc values and more rare codons 32 . The expression of highly biased genes is considered as high 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the M gene ENc value in SARS‐CoV‐2 was decreased by an amount of 3 to 5. Genes with low expression levels have high ENc values and more rare codons 32 . The expression of highly biased genes is considered as high 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that, U is preferred at the third 287 position specifically when G or C is present in the first two positions. On the contrary, when 288 the first two positions are taken by A or U; C is the 'right choice' (at third position) 38 . Thus, trnI(gat), trnI(gat) and trnQ(ttg), nad2 and trnW(tca), trnA(tgc) and trnN(gtt), trnS2(tga) and 315 trnD(gtc), trnD(gtc) and cox2, atp6 and cox3, nad3 and trnR(tcg), nad4 and trnH(gtg), 316 trnL1(tag) and nad5, nad5 and cob, cob and trnT(tgt), trnT(tgt) and trnP(tgg) (CR1) along 317 with trnP(tgg) and nad6 (Supplementary file 3).…”
Section: Nucleotide Composition and Translational Efficiency 243mentioning
confidence: 99%
“…This parameter measures the competence of codon-anticodon interactions indicating the 174 accuracy of the translational machinery of genes in the absence of preferred codon set 175 information. We calculated the translational efficiency according to the following equation 38 : 176…”
Section: Estimation Of Translational Efficiency 173mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in four non-grass monocot species also proposed that the G/C ending codons are optimal and that this preference is not likely caused by mutation biases [11]. Nevertheless, a recent study on four cotton species found the pattern that the pyrimidine-enriched codons (especially those ending with T) have higher frequency in the CDSs [12]. Meanwhile, it was also declared that the GC3 (GC content at the 3rd codon position) method was not always suitable for evolutionary comparisons at different scales [13] although CAI is positively correlated with GC3 [11].…”
Section: Introductionmentioning
confidence: 98%